O papel do Ministério Público no velamento das fundações: uma análise acerca da amplitude dos mecanismos de prestação de contas em uma perspectiva pluridimensional - Patzlaff, Airton Carlos (2013)
This dissertation investigates the extent of benefits of the accountability used by Parquet of Paraná State in the control of the Foundations of Private Law. Initially, it discusses the theoretical concepts of the Third Sector, as well as, it analyzes the documents present in the Public Prosecutor of the District of Pato Branco. Based on scientific considerations, it is clear that the control of foundations has multiple dimensions, which can be enhanced with tools that integrate the ontology of the Third Sector, together with the standards of the Parquet. The tools that can assist in the evaluation of the Third Sector, are: Balanced Scorecard, Social Balance, Ethos Indicators, SERVQUAL (Service Quality Framework), GET (Gap Evaluation Tool) and DEA (Data Envelopment Analysis). The data of this research indicated the limitations of the current methodology of accountability (SICAP), revealing how the controls used in the public and private sectors can transform the SICAP in a multidimensional method. Furthermore, the comparison of theory with empirical reality indicated ways to improve the foundational control exercised by the Public Prosecutor, giving guidelines for the implementation of a system of accountability broader, able to translate data into strategies. Therefore, the control method presented at the end of this research has its applicability confirmed, once that was used in the examination of two Foundations located in the District of Pato Branco, demonstrating the advantages of this methodology in the improvement of controls Parquet, and, in the development of the Third Sector.